Effect of Rumex Abyssinicus on preneoplastic lesions in dimethylhydrazine induced colon carcinogenesis in rats. Issue 1 (December 2015) - Girma, Biniyam; Yimer, Getnet; Makonnen, Eyasu
Abstract Background Cancer as a multistage process can be reversed or blocked by using chemopreventive agents. Colon cancer chemoprevention has been widely investigated using cyclooxygenase inhibitors and many other chemicals of synthetic or natural origin. This particular study was carried out to assess the colon cancer chemopreventive effect of hydro-methanol extract ofRumex abyssinicus rhizome on rats. Method Colon cancer chemopreventive potential of hydro-methanol extract ofRumex abyssinicus rhizome was determined based on the number and multiplicity of aberrant crypt foci (ACF). Fifteen DMH (1, 2-dimethylhydrazine) treated and five untreated Wistar female rats were used. DMH was administered subcutaneously 30 mg/kg, after its pH was adjusted to 6.5–7. Treatment groups started receiving extract after six weeks of weekly DMH injections. The rats were divided in to four groups: Group 1 received only oral normal saline, Group 2 received DMH and normal saline, Group 3 and 4 received DMH plus 250 mg/kg and 500 mg/kg extract, respectively. Specific phytoconstituents of the plant, which were reviewed from original articles, were virtually evaluated for cyclooxygenase-2 (COX-2) inhibition. The binding energies and interactions of the phytochemicals fromRumex abyssinicus against COX-2 were determined by Autodock4.2. Results There was a statistically significant reduction(p-value < 0.05) in the number of aberrant crypt (AC) and aberrant crypt foci (ACF) at both administered doses. However, significant association(p-value > 0.05) was not observed in reducing crypt multiplicity. The docking process resulted in estimated binding energies [−6.83 kcal/mol to −7.9 kcal/mol] which are closer to the positive controls or Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) [−4.55 kcal/mol to −10.84 kcal/mol]. The phytochemical-COX-2 interaction indicated the involvement of key amino acid residues in inhibition of cyclooxygenase like ARG120, TYR355, TYR385, SER530 and GLY526. Conclusions Rumex abyssinicus had demonstrated a chemopreventive potential at post-initiation stage. As the virtual screening data suggested, COX-2 inhibition by the anthraquinones in the extract could be one mechanism for the observed chemopreventive effect.